Data_Sheet_1_Dietary Factors and Risk of Glioma in Adults: A Systematic Review and Dose-Response Meta-Analysis of Observational Studies.docx - Weichunbai Zhang; Jing Jiang; Xinyi Li; Yongqi He; Feng Chen; Wenbin Li (2022)
Background Gliomas are the most common primary intracranial tumors in adults. Inappropriate dietary habits are thought to be a risk factor for most human cancer, and glioma is no exception. However, the effect of dietary factors on glioma is not clear. Objective This review aims to quantitatively evaluate the association between various dietary intakes and glioma using a meta-analysis. Methods We searched articles on PubMed, the Cochrane Library, the Web of Science, and EMBASE from their inception until October 11, 2021. According to heterogeneity, the fixed-effects or random-effects model was selected to obtain the relative risk (RR) of merger. Based on the methods described by Greenland and Longnecker, we explored the dose-response relationship between dietary intakes and the risk of glioma. Subgroup analysis, sensitivity analysis, and publication bias were also used. Results This study reviewed 33 articles, including 3,606,015 controls and 8,831 patients with glioma. This study included 12 food groups. Compared with the lowest intakes, the highest intakes of tea (RR = 0.82, 95%CI:0.71–0.93), total vegetables (RR = 0.84, 95%CI: 0.70–1.00), green vegetables (RR = 0.80, 95%CI: 0.66–0.98), and orange vegetables (RR = 0.79, 95%CI: 0.66–0.96) significantly reduced the risk of glioma, while the highest intakes of grains (RR = 1.39, 95%CI: 1.16–1.66), processed meats (RR = 1.19, 95%CI: 1.00–1.42), and processed fish (RR = 1.37, 95%CI: 1.03–1.84) significantly increased the risk of glioma. The results of subgroup and sensitivity analyses remained unchanged. In the dose-response relationship, only tea was statistically significant. Taking an extra cup of tea every day reduced the risk of glioma by 4%. Conclusions Our analysis suggests that the intakes of tea, total vegetables, green vegetables, and orange vegetables may reduce the risk of glioma, while the intakes of grains, processed meats, and processed fish may increase the risk of glioma. Therefore, the effect of dietary factors on glioma should not be ignored. ...